Quality of life and multimorbidity of elderly outpatients (Clinics, 2009)
INTRODUCTION: Substantial medical research has established an inverse relationship between quality of life and illness. However, there exists minimal evidence for such a connection in the context of stable and controlled diseases. OBJECTIVE: We wished to correlate multimorbidity with quality of life for elderly patients who suffer from stable chronic diseases. METHODS: We used a tool to evaluate quality of life, namely World Health Organization quality of life-BRIEF, together with a scale of multimorbidity known as the Cumulative Illness Rating Scale - Geriatric Version. Furthermore, the quality of life data were correlated with scores recorded on the Cumulative Illness Rating Scale - Geriatric Version, the number of drugs used, and individual perceptions of health and age. RESULTS: We studied 104 elderly patients who suffered from chronic diseases. The patients had exhibited neither acute events nor secondary complications, their cognition was intact, and they were functionally independent. The Cumulative Illness Rating Scale - Geriatric Version showed an inverse correlation with the physical domain (p= 0.008) and a tendency toward an inverse correlation with the psychological domain (p= 0.052). Self-perception of health showed a high correlation with the physical domain (p= 0.000), psychological domain (p= 0.000) and environmental domain (p= 0.000). The number of drugs used correlated only with the physical domain (p= 0.004). Age and social domain showed a tendency toward a positive correlation (p= 0.054). DISCUSSION: We uncovered an inverse relationship between quality of life and multimorbidity in a group of patients who suffered from stable chronic diseases, with no functional limitations, pain or complications. Our data suggest that a patient's knowledge that they have a certain clinical condition changes their subjective assessment of quality of life in the related domain. CONCLUSION: The perceived quality of life of the sample was affected by multimorbidity in the physical domain, with a tendency toward commensurate effects in the psychological domain.